Concurrent training in prepubertal children: different combination approaches between resistance and aerobic training in physical fitness variables - Alves, Ana Sofia Ruivo (2018)
Concurrent training has been investigated over the last three decades, amongst scientific community. This is an interesting topic for researchers due to the controversial results in literature, specifically in a school environment. Therefore, the purpose of this work was to analyze the effects of different combination approaches between resistance and aerobic training on explosive strength and aerobic capacity in a large sample of prepubertal children. Additionally, we intended to investigate the effects of training exercise mode alone on overall physical fitness in prepubertal children. For the accomplishment of these purposes the following sequence was used: i) reviewing the available literature; ii) assessing three different training methods (intra-session concurrent training, concurrent training in different sessions, and resistance training alone) and analyzing their effects on explosive strength and VO2max adaptations; iii) comparing two different intra-session concurrent training sequences on explosive strength and VO2max during 8-weeks training period; iv) proposing multiple linear regression models for determining distinct strength parameters and VO2max performances according to specific training programs with 8-weeks duration. The main conclusions found suggest that i) there is a limited research on training-induced physical fitness variables in prepubertal children; ii) the concurrent training performed in different sessions can be performed without implications on prepubertal children’ growth, as it is also effective for training-induced explosive strength and VO2max; iii) the concurrent training (intra-session or different sessions) and resistance training alone provide similar neuromuscular adaptations in prepubertal girls and boys; iv) the intra-session concurrent training, regardless the order, improve prepubertal children performance on explosive strength and VO2max; v) it is possible to develop indirect predictive models for each training method with 8-weeks duration. Our findings provide useful remarks about the effects of different combination approaches between resistance and aerobic training on explosive strength and aerobic capacity in prepubertal children. These results can be helpful for coaches, teachers and researchers to optimize explosive strength and cardiorespiratory fitness training in sports club and school-based programs, as well as a reliable source for further researches.